2016
DOI: 10.1016/j.msec.2015.09.084
|View full text |Cite
|
Sign up to set email alerts
|

Neurotypic cell attachment and growth on III-nitride lateral polarity structures

Abstract: III-nitride materials have recently received increasing levels of attention for their potential to successfully interface with, and sense biochemical interactions in biological systems. Expanding on available sensing schemes (including transistor-based devices,) a III-N lateral polarity structure capable of introducing quasi-phase matching through a periodic polarity grating presents a novel platform for second harmonic generation. This platform constitutes a non-linear optical phenomenon with exquisite sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…This instability increases the amount of surface‐adsorbed proteins on N‐polar surfaces which allows for easier cellular attachment. This is in agreement with our prior work where we have reported that PC12 cells show the highest adherent density when the lateral polarity structures size is less than the cell size of 10–12 µm . In this particular surface design since the Ga‐polar regions were 100 µm in diameter, cells did not adhere to them regardless of chemical treatment or UV light exposure.…”
supporting
confidence: 92%
“…This instability increases the amount of surface‐adsorbed proteins on N‐polar surfaces which allows for easier cellular attachment. This is in agreement with our prior work where we have reported that PC12 cells show the highest adherent density when the lateral polarity structures size is less than the cell size of 10–12 µm . In this particular surface design since the Ga‐polar regions were 100 µm in diameter, cells did not adhere to them regardless of chemical treatment or UV light exposure.…”
supporting
confidence: 92%
“…[24,25] The wide application of GaN/AlGaN in monitoring cellular electrical signals [26][27][28] highlights the promising potential of these systems as new generation electronic biomaterials for regenerative medicine that can simultaneously stimulate, manipulate, and record cell bioelectrical activity in vitro and in vivo. [29] Finally, a growing number of studies show that GaN and AlGaN possess excellent biocompatibility and biosafety, [30][31][32][33] which are basic properties of biomaterials. Therefore, we propose that GaN/ AlGaN with well-controlled surface polarity could serve as a powerful tool for inducing endogenous electric stimulation to accelerate and improve bone regeneration; this system could also serve as a potential research platform to study the influence of surface charge on cell behavior.…”
Section: Introductionmentioning
confidence: 99%
“…36−38 In our own work with the same materials we have demonstrated that surface roughness can be an important factor in cell adhesion. 39,40 Therefore, we assess the surface characteristics of GaN samples with two different doping concentrations (GaN m(edium) and GaN h(igh) ) that were either treated or not treated with UV light. We characterized the roughness of clean GaN samples using AFM topography imaging.…”
Section: Resultsmentioning
confidence: 99%
“…We began this work by hypothesizing that the accumulation of charge on the surface of inorganic samples is a significant way to manipulate the response of biological system formed on a GaN surface. However, prior work has shown that bacterial film formation and behavior can be manipulated by other interfacial characteristics such as surface roughness. In our own work with the same materials we have demonstrated that surface roughness can be an important factor in cell adhesion. , Therefore, we assess the surface characteristics of GaN samples with two different doping concentrations (GaN m(edium) and GaN h(igh) ) that were either treated or not treated with UV light. We characterized the roughness of clean GaN samples using AFM topography imaging.…”
Section: Resultsmentioning
confidence: 99%